Who is Guilty? Ideologies of Communication, Narratives and Moral Discourse in the Combat against Tuberculosis in a Peruvian Prison - Portocarrero, Julio (2020)
This paper discusses the narratives, dialogues and experiences of inmates and health personnel involved in an intervention funded by the Global Fund to reduce tuberculosis rates in Peruvian prisons. It seeks to answer two main questions: How is it discussed and who has the responsibility for care of the disease in this intervention? It is based on an ethnography conducted in 2006 in Lurigancho, the most overcrowded prison in Peru. The study shows that, contrary to what interventionists affirm, most of the inmates can reproduce the biomedical versions of the disease’s etiology in their own terms and without major problems,. It was found that intervention discourse holds the patient solely responsible for his health condition; obscuring other equally important social and economic factors. It is argued that many public health policies have taken on a reductionist nature since they have begun to be based upon liberal economic assumptions. As a consequence of this process, certain diseases and types of patients or social groups are considered as morally reprehensible and punishable. It is concluded that it is essential to explore the communication ideology behind any intervention or public health policy.